PKM Implementation: Collaboration between Lecturers and Students in the Development of Spinach Sticks as a Diversification of Local Processed Food Products: Implementasi PKM: Kolaborasi DPL dan Mahasiswa dalam Pengembangan Produk Stick Bayam untuk Diversifikasi Produk Olahan Pangan Lokal - Mustaqim Makki; Subairi; Nur, Achmad (STAI Nurul Huda Kapongan Situbondo, 2025)
Local processed food product diversification can improve both product diversity and food security. Nutrient-dense spinach sticks are one of the novelties created. The lack of variation in spinach processing and student participation in the creation of regional goods are the issues at hand. Therefore, in order to build this product, students and Field Supervisors (DPL) must work together. Utilizing local potential, such as spinach as the raw material, the Asset-Based Community Development (ABCD) approach is the methodology employed. Under the direction of the DPL, students and the community participated in training to make spinach sticks. Product design, appraisal, and market research are all part of this process. This led to the successful development of the spinach stick product, which might potentially be marketed. This program provides new nutrient-dense foodstuffs and improves pupils' abilities to process local food. This product is intended to promote more varied local culinary ideas.